2017
DOI: 10.3389/fpsyg.2017.00535
|View full text |Cite
|
Sign up to set email alerts
|

When a Fly Ball Is Out of Reach: Catchability Judgments Are Not Based on Optical Acceleration Cancelation

Abstract: The optical acceleration cancelation (OAC) strategy, based on Chapman’s (1968) analysis of the outfielder problem, has been the dominant account for the control of running to intercept fly balls approaching head on. According to the OAC strategy, outfielders will arrive at the interception location just in time to catch the ball when they keep optical acceleration zero. However, the affordance aspect of this task, that is, whether or not an approaching fly ball is catchable, is not part of this account. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…It is crucially important to appreciate the subtle distinction with actions or movements being controlled by information, as ecological psychologists have traditionally argued (e. g., Lee, 1976;Michaels & Oudejans, 1992;Peper et al, 1994;Warren, 1988). Take forexample, anoutfielderinbaseball running to catch a fly ball (Postma, Smith, Pepping, van Andel, & Zaal, 2017; see also Fajen, 2007). According to a widely Abstract The goalkeeper's difficulty in the soccer penalty kick originates from the extreme spatiotemporal constraints of the situation.…”
Section: The Affordance-based Control Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucially important to appreciate the subtle distinction with actions or movements being controlled by information, as ecological psychologists have traditionally argued (e. g., Lee, 1976;Michaels & Oudejans, 1992;Peper et al, 1994;Warren, 1988). Take forexample, anoutfielderinbaseball running to catch a fly ball (Postma, Smith, Pepping, van Andel, & Zaal, 2017; see also Fajen, 2007). According to a widely Abstract The goalkeeper's difficulty in the soccer penalty kick originates from the extreme spatiotemporal constraints of the situation.…”
Section: The Affordance-based Control Theorymentioning
confidence: 99%
“…The ball is only perceived as catchable for the fielder if she or he can run fast enough to cover the distance to the interception location in time. If the required running velocity exceeds the running speed that the outfielder can achieve (or maintain), then the fly ball is no longer perceived as catchable-in that case the outfielder is perhaps better off preparing to get the ball after a bounce (Postma et al, 2017). Consequently, to be successful, the outfielder must run in Review order to ensure that the required running velocity is kept within the limits of her or his running capabilities, that is, within the action boundaries.…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…Fajen et al found that subjects' judgments were no more accurate when moving than when standing still. 1 More recent work investigating the interception of fly balls casts further doubt onto the current-future account (Postma, Lemmink, & Zaal, 2018;Postma, Otter, & Zaal, 2014;Postma, Smith, Pepping, van Andel, & Zaal, 2017). Postma et al (2017) found that at the moment that subjects reported fly balls as uncatchable, they were running at less than half of their maximum speed with negligible acceleration.…”
Section: Perception Of Catchability From the Current-future Perspectivementioning
confidence: 99%
“…1 More recent work investigating the interception of fly balls casts further doubt onto the current-future account (Postma, Lemmink, & Zaal, 2018;Postma, Otter, & Zaal, 2014;Postma, Smith, Pepping, van Andel, & Zaal, 2017). Postma et al (2017) found that at the moment that subjects reported fly balls as uncatchable, they were running at less than half of their maximum speed with negligible acceleration. Such responses are inconsistent with any current-future account of perceiving catchability, including one based on the fly ball's optical acceleration, the dominant model for interception of a fly ball (Chapman, 1968;Fink, Foo, & Warren, 2009;Michaels & Oudejans, 1992), and are better explained from an affordance-based perspective (Postma et al, 2018).…”
Section: Perception Of Catchability From the Current-future Perspectivementioning
confidence: 99%
See 1 more Smart Citation